Top-down vs. bottom-up? Reconciling the effects of tax and transfer shocks on output - Sebastian Gechert; Christoph Paetz; Paloma Villanueva (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
Using the bottom-up approach of Romer and Romer (2010), we construct a rich narrative dataset of net-revenue fiscal shocks for Germany by reconstructing and extending the tax shock series of Hayo and Uhl (2014) and coding a shock series for social security contributions, benefits and transfers. Based on quarterly data for 1974q1 to 2013q4 we estimate the multiplier effects of shocks to net-revenues, taxes, social security contributions and benefits in a proxy SVAR framework (Mertens and Ravn 2013) and compare them with estimates of the top-down identification inspired by Blanchard and Perotti (2002). We find multiplier effects of net-revenue components for Germany between 0 and 1 for both the top-down and bottom-up approaches. These estimates are on the lower end of the scale given in the literature and we discuss the differences. – – Aus Informationen von Gesetzesänderungen konstruieren wir einen umfangreichen narrativen Datensatz exogener fiskalpolitischer Schocks für Deutschland (Bottom-Up-Ansatz von Romer und Romer 2010). Dafür reproduzieren und erweitern wir die existierende Schockserie für Steuerrechtsänderungen von Hayo und Uhl (2014) und ergänzen sie durch eine selbst kodierte Zeitreihe für die Sozialgesetzgebung. Mit diesen Daten schätzen wir für den Zeitraum 1974q1 bis 2013q4 die Multiplikatoreffekte von Nettoeinnahme-, Steuer-, Sozialversicherungsbeitrags- und Transfer-Schocks in einem Proxy-SVAR-Ansatz (Mertens und Ravn 2013). Wir vergleichen die Ergebnisse mit Schätzungen, in denen die Schocks nach einem Top-Down-Ansatz identifiziert werden (Blanchard und Perotti 2002). Wir finden für Deutschland Multiplikatoreffekte zwischen 0 und 1 für diese Nettoeinnahmekomponenten - sowohl im Top-Down als auch im Bottom-Up-Ansatz. Diese Schätzungen liegen eher am unteren Ende der Skala in der Literatur und wir diskutieren die Unterschiede.
urn:nbn:de:101:1-20160614727
Keywords: E62; H20; H30; 330; Narrative Record Identification; Action-Based Approach; Fiscal Multipliers; Revenue Elasticities